Socio-Cultural Practices During Menstruation Among Adolescent Girls - Acharya, Muna; Timalsina, Keshab Prasad (International Research Journal of MMC, 2025)
Menstrual health is a stigmatized but critical concern in Nepal, where adolescent girls face numerous socio-cultural restrictions despite increasing education. The study tried to analyze the knowledge level and prevalence of restrictive practices at menstruation among adolescent girls in schools. This cross-sectional study investigates the awareness levels of menstrual hygiene and the prevalence of socio-cultural restrictions among 147 adolescent girls in grades 8 to 12 at Pragati Higher Secondary School, Hetauda-9, Nepal. Using stratified random sampling, data were collected through structured questionnaires to assess knowledge, practices and restrictive traditions associated with menstruation. Findings revealed that although the majority of girls possessed rudimentary knowledge of menstrual hygiene, socio-cultural restrictions were practiced everywhere, 87.8% avoided religious events, 61.9% stayed away from kitchen activities, and 62.3% practiced food taboos. While 91.8% hated these taboos, they still existed due to social pressures. ANOVA analysis showed no statistically significant variation in knowledge levels by socio-demographic variables such as age, grade, religion, or parental education. Comparative analysis with previous studies confirmed that awareness does not necessarily lead to practice. The discussion highlighted how deep-rooted patriarchal norms shape menstrual behaviors beyond individual knowledge. The study calls for institutional reforms and culturally sensitive interventions. Further research should include male perspectives and assess long-term impacts of educational efforts.